Loading...

its 2

It equals 6

100101 1 times 2^0 = 1 PLUS 0 times 2^1 = 0 PLUS 1 times 2^2 = 4 PLUS 0 times 2^3 = 0 PLUS 0 times 2^4 = 0 PLUS 1 times 2^5 = 32 EQUALS 37

It is: (1+1)*(0+1) = 2

1+-1= 0. 0+1=1 1+2=3 ps 3+4=7 7+8=15

The sum of 2 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 equals 2.

1 + 1 - 2 = 0

2 x 0 x 1 + 1 = 0 + 1 = 1

because when you add 1 to 0 it is 2

1 + 1 = 2 1 = 2 - 1 1 + 1 - 2 = 0 0 = 2 - 1 - 1

As stated it is just an algebraic expression. However, if we equate it to zero then it can be solved. 2a2 + 5a + 2 = 0 This can be factored (2a + 1)(a + 2) = 0 This means that (2a + 1) = 0 or (a + 2) = 0 Then either 2a = -1 : a = -1/2 or a = -2

0=(9)2-(9-3)(root of 4)+3(2)

Any value times 0 is 0 so 0 + 1 = 1

The answer is 0.

x^2 + 1 = 0 x^2 - (-1) = 0 x^2 - i^2 = 0 (x - i)(x + i) = 0 x = i or x = -i

The answer is 0 because at the end it is multiplied by 0

-1 plus 1 = 0 plus 1 =1

43

Anything multiplied by 0 is 0, so all the ones before the 0 can be ignored. It is now 0+1 which equals 1.

It is closer to 1 than it is to 0.

x2-x3+2x = 0 x(-x2+x+2) = 0 x(-x+2)(x+1) = 0 Points of intersection are: (0, 2), (2,10) and (-1, 1)

Another Answer: 12*0+1 = 1

12 + 1a - 1a + 1 = 1 + 0 + 1 = 2

6 - 1 * 0 + 2 / 2 = 7

8/8 - 1 + 3 - 1 + 0 = 1-1+3-1+0 = 0 + 3 - 1 + 0 = 3 - 1 = 2